Molecular Characterization of the Lactococcus lactis LlaKR2I Restriction-Modification System and Effect of an IS982 Element Positioned between the Restriction and Modification Genes - Twomey, Denis P. (American Society for Microbiology, 1998)
The nucleotide sequence of the plasmid-encoded LlaKR2I restriction-modification (R-M) system of Lactococcus lactis subsp. lactis biovar diacetylactis KR2 was determined. This R-M system comprises divergently transcribed endonuclease (llaKR2IR) and methyltransferase (llaKR2IM) genes; located in the intergenic region is a copy of the insertion element IS982, whose putative transposase gene is codirectionally transcribed with llaKR2IM. The deduced sequence of the LlaKR2I endonuclease shared homology with the type II endonuclease Sau3AI and with the MutH mismatch repair protein, both of which recognize and cleave the sequence 5′ GATC 3′. In addition, M · LlaKR2I displayed homology with the 5-methylcytosine methyltransferase family of proteins, exhibiting greatest identity with M · Sau3AI. Both of these proteins shared notable homology throughout their putative target recognition domains. Furthermore, subclones of the native parental lactococcal plasmid pKR223, which encode M · LlaKR2I, all remained undigested after treatment with Sau3AI despite the presence of multiple 5′ GATC 3′ sites. The combination of these data suggested that the specificity of the LlaKR2I R-M system was likely to be 5′ GATC 3′, with the cytosine residue being modified to 5-methylcytosine. The IS982 element located within the LlaKR2I R-M system contained at its extremities two 16-bp perfect inverted repeats flanked by two 7-bp direct repeats. A perfect extended promoter consensus, which represented the likely original promoter of the llaKR2IR gene, was shown to overlap the direct repeat sequence on the other side of IS982. Specific deletion of IS982 and one of these direct repeats via a PCR strategy indicated that the LlaKR2I R-M determinants do not rely on elements within IS982 for expression and that the efficiency of bacteriophage restriction was not impaired.